ANALISIS RANTAI PASOK KOMODITAS CABAI RAWIT DUSUN SUPITURANG DESA BOCEK KABUPATEN MALANG - Bastyan, Robertus Abel Sefto; Sa’diyah, Ana Arifatus; Masduki, Said (Fakultas Pertanian, 2019)
Supply chain is a regulatory system concept related to product flow , information and finance. This study aims to analyze and supply chain performance of raw chili commodities in Supiturang Hamlet, Bocek Village. The data analysis method used is descriptive quantitative. The sampling technique uses Census and Snowball Sampling. Data obtained by direct interviews and questionnaires accompanied by documentation. Flow 1 of the supply chain starts from the farmer sells to the collector then the collector sells to the wholesaler then the wholesaler sells to the retailer and consumer the last ABC factory is sold to the consumer. Flow 2 starts from the farmer sells to the collector then the collector sells to the retailers and consumers of the ABC factory finally sold to consumers. Analysis of supply chain performance in this study includes analysis of farming, marketing margins and farmer's share. The results of farming analysis obtained 1.69. The biggest marketing margin is in flow 1 which is 16,500 IDR / Kg. The flow of 2 supply chains has the highest efficiency value of 42%. From the results of the study, if the supply chain flow is carried out by each marketing agency, it will be more profitable and will be more profitable for farmers and in the analysis of chili cultivation, it is quite profitable. Rantai pasok merupakan konsep sistem pengaturan yang berkaitan dengan aliran produk, informasi dan keuangan. Penelitian ini bertujuan untuk menganalisis dan kinerja rantai pasok komoditas cabai rawit Dusun Supiturang Desa Bocek. Metode analisis data yang digunakan adalah deskriptif kuantitatif. Teknik pengambilan sampel menggunakan Sensus dan Snowball Sampling. Data diperoleh dengan cara wawancara langsung dan kuisioner disertai dokumentasi. Aliran 1 rantai pasok dimulai dari petani menjual ke pengumpul kemudian pengumpul menjual ke pedagang besar selanjutnya pedagang besar menjual ke pengecer dan konsumen pabrik ABC terakhir dijual ke konsumen. Aliran 2 dimulai dari petani menjual ke pengumpul kemudian pengumpul menjual ke pedagang pengecer dan konsumen pabrik ABC akhirnya dijual ke konsumen. Analisis kinerja rantai pasok dalam penelitian ini meliputi analisis usahatani, margin pemasaran dan farmer’s share. Hasil analisis usahatani memperoleh 1,69. Margin pemasaran terbesar terdapat pada aliran 1 yaitu 16.500 Rp/Kg. Aliran 2 rantai pasok mempunyai nilai efisiensi tertinggi 42%. Dari hasil penelitian, apabila aliran rantai pasok dilakukan setiap lembaga pemasaran semakin pendek akan lebih menguntungkan petani dan pada analisis usahatani budidaya cabai rawit tersebut cukup menguntungkan untuk dilakukan.